Juridical Reviewlegal Protection of Employees Subject To Termination - Kiko Chandra Dwiwardana; Mohammad Roesli; Bastianto Nugroho (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
The purpose of this research is to find out the legal arrangements for termination of employment (PHK) according to Law no. 11 of 2020 Concerning Job Creation. This research uses the method The type of research in this study is normative juridical law research, namely research based on literature studies which includes primary legal materials and secondary legal materials. As a result, a worker is given protection or a job loss guarantee in accordance with Article 28D paragraph (1) of the 1945 Constitution. This job loss guarantee is also regulated in the Regulation of the Minister of Manpower of the Republic of Indonesia number 15 of 2021 where it states that Job Loss Benefit is social security given to workers who experience layoffs in the form of cash benefits, access to job market information, and job training. The protection given to workers aims to achieve the rights that workers will receive. And this can be a reference for workers if one day they lose their jobs. And the reason why workers are given protection is to minimize the unemployment rate that occurs in Indonesia. If a company/employer wants to terminate their employment relationship with workers, the impact on the company is that the company must provide severance pay, compensation for years of service, and compensation for rights to workers in accordance with applicable laws and regulations.